KOMPARASI TRADISI LINGUISTIK HALLIDAY VERSUS TRADISI LINGUISTIK CHOMSKY - Teddy Yusuf (JURNAL ISTEK, 2012)
This is a study of research library (studi kepustakaan). The data used in this research are the primer and secondary data in the form of written material (some accounts of Chomsky and Halliday) which is related to the topic discussed. The primer source used in this research are Aspects of the Theory of Syntax and An Introduction to Functional Grammar. This research focus on the tradition of Chomskyan Linguistik and Hallidayan Linguistic. This research used analytic descriptive method on the level of theory critique. The aims of the research are to find out the comparison between the some features of Chomskyan and Hallidayan Linguistic. Results of research concluded the fundamental difference from Chomskyan and Hallidayan linguistics as follow: Functional Grammar focus on the purposes and uses of language. They derive from examination of spoken and written language and the context of their use. The aim of FG include; (1) revealing many of the choices language users have in interaction (2) showing how meaning is made. Whereas Transformational Grammar focus on the facts that all speaker of natural language (e.g. English, Javanesse, Sundanesse, etc.) are able to form new sentences and understand utterances they have never heard before. According to TG knowing language is not merely a matter of storing in one’s head a long list of words or sentences, but being able to produce sentences not heard before. The results of this research is relevant for the language teaching, especially for teaching English language.